ALMA observations of the narrow HR 4796A debris ring. Issue 4 (16th January 2018) - Kennedy, Grant M; Marino, Sebastian; Matrà, Luca; Panić, Olja; Wilner, David; Wyatt, Mark C; Yelverton, Ben
Abstract: The young A0V star HR 4796A is host to a bright and narrow ring of dust, thought to originate in collisions between planetesimals within a belt analogous to the Solar system's Edgeworth–Kuiper belt. Here we present high spatial resolution 880 μm continuum images from the Atacama Large Millimeter Array. The 80 au radius dust ring is resolved radially with a characteristic width of 10 au, consistent with the narrow profile seen in scattered light. Our modelling consistently finds that the disc is also vertically resolved with a similar extent. However, this extent is less than the beam size, and a disc that is dynamically very cold (i.e. vertically thin) provides a better theoretical explanation for the narrow scattered light profile, so we remain cautious about this conclusion. We do not detect 12 CO J =3–2 emission, concluding that unless the disc is dynamically cold the CO+CO2 ice content of the planetesimals is of order a few per cent or less. We consider the range of semi-major axes and masses of an interior planet supposed to cause the ring's eccentricity, finding that such a planet should be more massive than Neptune and orbit beyond 40 au. Independent of our ALMA observations, we note a conflict between mid-IR pericentre-glow and scattered light imaging interpretations, concluding that models where the spatial dust density and grain size vary around the ring should be explored.